Analisis Tingkat Kesehatan PT.BNI Syariah dengan Menggunakan Rasio Keuangan yaitu Rasio Likuiditas dan Economic Value Added (EVA) - Sabirin Sabirin; Desy Agus Saputri (Department of Accounting-Faculty of Economic and Business (FEB), 2021)
The purpose of this study was to determine the soundness of Islamic banks by using financial ratios, namely the liquidity ratio and Economic Value Added (EVA). The object of this research is the BNI Syariah Bank Financial Report for the 2016-2019 research period. The analysis technique used is the liquidity ratio and Economic Value Added (EVA). The results of the study show that the health level of the liquidity ratio which consists of the 2016 to 2019 Quick Ratio is in an unhealthy position. Cash Ratio from 2016 to 2019 is in a very healthy position. Loan to Deposit Ratio from 2016 to 2018 is in a healthy position. Lastly, the Banking Ratio in 2018 and 2019 is in a healthy position, while in 2016 and 2017 it is in an unhealthy position. Meanwhile EVA in 2016 to 2019 showed a positive value or EVA > 0 meaning that it succeeded in creating economic value addedHow to Cite:Sabirin., & Syaputri, D. A. (2021). Analisis Tingkat Kesehatan PT. BNI Syariah Periode 2016-2019. Akuntabilitas: Jurnal Ilmu Akuntansi, 14(2), 187-200.